2007
DOI: 10.1016/j.compstruct.2006.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Improving strength of postbuckled panels through stitching

Abstract: The behavior of blade-stiffened graphite-epoxy panels with impact damage is examined to determine the effect of adding through-the-thickness stitches in the stiffener flange-to-skin interface. The influence of stitches is evaluated by examining buckling and failure for panels with failure loads up to 3.5 times greater than buckling loads. Analytical and experimental results from four configurations of panel specimens are presented. For each configuration, two panels were manufactured with skin and flanges held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The reduction of in-plane properties is minimized by stitching structural elements where the delamination due to interlaminar peel stresses at the joined regions are the most critical. 15 Delamination due to interlaminar peel stresses are the primary form of failure in overlapping joints, and stitching has shown to increase the lap joint 12 strength by approximately 60% to 175%. [15][16][17][18][19][20][21][22][23] Quasistatic structural testing of notched PRSEUS panels has also shown that the selective stitching approach allows unitized structural members to effectively arrest delaminations from barely visible impact damage and translaminar crack growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction of in-plane properties is minimized by stitching structural elements where the delamination due to interlaminar peel stresses at the joined regions are the most critical. 15 Delamination due to interlaminar peel stresses are the primary form of failure in overlapping joints, and stitching has shown to increase the lap joint 12 strength by approximately 60% to 175%. [15][16][17][18][19][20][21][22][23] Quasistatic structural testing of notched PRSEUS panels has also shown that the selective stitching approach allows unitized structural members to effectively arrest delaminations from barely visible impact damage and translaminar crack growth.…”
Section: Introductionmentioning
confidence: 99%
“…15 Delamination due to interlaminar peel stresses are the primary form of failure in overlapping joints, and stitching has shown to increase the lap joint 12 strength by approximately 60% to 175%. [15][16][17][18][19][20][21][22][23] Quasistatic structural testing of notched PRSEUS panels has also shown that the selective stitching approach allows unitized structural members to effectively arrest delaminations from barely visible impact damage and translaminar crack growth. 14 As a result of this research, a significant amount of exploration of the out-of-plane behavior of stitched polymer composites was performed in 2007 15,18,19,[24][25][26][27][28][29][30][31][32][33][34][35] and 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STAGS post-buckling capability was used on bladestiffened and PRSEUS panels. 1,[3][4][5][6][7][8][9][11][12][13][1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]20 Examples of these specimens are shown in Fig. 6 …”
Section: A Predicting Post-bucking Behaviormentioning
confidence: 99%
“…Buckling analyses are typically conducted on compression-loaded specimens to determine the bifurcation buckling load and initial mode shape but nonlinear analysis is often required to determine how much load the structure will carry and quantify its post-buckling behavior since stitched structure has demonstrated an ability to support load beyond buckling. 4,6,[11][12][13][14][15][16][17][18][19][20] Nonlinear analysis can be conducted until collapse is reached and this result is compared to test data.…”
Section: Modeling and Analyzing Stitched Structures In Stagsmentioning
confidence: 99%